Kesan penggunaan geogebra terhadap keupayaan visualisasi spasial dan kemahiran berfikir dalam pembelajaran bentuk dan ruang - Khor, Mui Kim (2018)
The results of Trends in International Mathematics and Science Study (TIMSS) from 1999 until 2011 showed a decline in Malaysia 8th grade students’ Mathematics achievement. This drop was attributed to the lack of spatial visualization ability and thinking skills in mathematics learning among the students. Currently, few research has been done on the use of GeoGebra dynamic software in the learning mathematics in Malaysia. The aim of this study is to determine the effect of using GeoGebra dynamic software (Independent Variable) on thinking skills (Dependent Variable) and spatial visualization ability (Dependent Variable) in the learning of Shape and Space. This quasi-experiment design used pre and post-test design whereby the Spatial Visualization Ability Test and the Shape and Space Test were administered. The quantitative data was analyze using MANOVA, whereas the qualitative data was obtained via semi-structured interviews, observation and video recordings, was transferred into transcripts and thematically analyze. A total of 102 Form Two daily school students participated in this study and they were divided into three research groups, whereby 33 students in the Experimental Group 1, 35 students in the Experimental Group 2 and 34 students were in the Control Group. A guideline book, entitled Using GeoGebra Dynamic Software in learning of Shape and Space, was developed by the researcher. This book was used in the experimental groups along the research. The findings indicate that students had higher spatial visualization ability and thinking skills in learning shape and space that integrates GeoGebra dynamic software. Students’ works indicated their applying, analyzing, evaluating and creative cognitive skills, with creative and innovative elements. This study contributes to the theory of Van Hiele which is the basis for the development of geometry learning curriculum. The study also contributes to students’ knowledge and skills in using GeoGebra dynamic software in learning Mathematics that integrates technology.